A scenario-based coupled SWAT-MODFLOW decision support system for advanced water resource management. Issue 1 (26th October 2021) - Izady, A.; Joodavi, A.; Ansarian, M.; Shafiei, M.; Majidi, M.; Davary, K.; Ziaei, A. N.; Ansari, H.; Nikoo, M. R.; Al-Maktoumi, A.; Chen, M.; Abdalla, O.
Abstract: Models provide invaluable visions to decision-makers for basin-scale management of water resources. However, decision-makers have difficulties in directly using these complex models. Water managers are primarily interested in user-friendly features allowing an integration of their judgments into the decision-making process, rather than applying detailed theories and methodologies. This knowledge gap between technical simulation models and policy-makers highlights the urgent need for developing an integrated water resource management decision support system (IWRM-DSS). This paper describes the main aspects of a new IWRM-DSS in which Microsoft Visual Studio under the C# language was employed to integrate the Microsoft SQL server as a database and ArcGIS Engine DLLs for pre/postdata processing for the SWAT and MODFLOW models. Two particular 'module' and 'presentation' shells are specifically designed for decision-makers to create four different scenarios, namely, 'climatic', 'recharge', 'discharge', and 'coupled' and to analyze the results. Decision-makers, without any detailed modeling knowledge and computer skills, can access the data and run models to test different management scenarios in an attractive graphical user interface. The IWRM-DSS, which was applied for the Neishaboor watershed, Iran, reveals that mean annual potential evapotranspiration increased to 8.2%, while runoff and recharge rates are reduced to 35 and 63%, which led to a decline of 13.5 m in mean groundwater level for the 13-year projected period. HIGHLIGHTS: Decision-makers have difficulties in directly using complex simulation models. Decision-makers prefer the integration of their judgments into the decision-making process. A scenario-based coupled SWAT-MODFLOW Decision Support System was developed. Decision-makers can test different scenarios without any detailed modeling knowledge. The DSS was efficient to engage stakeholders in the water resource management process. Graphical Abstract